Georges Bataille : art, origine et transgression dans les peintures de Lascaux - Gabrysiak, Diane (Romanica Silesiana)
In 1955 Georges Bataille published two books on art : Manet located the origin of modernism in Manet’s work, while the other, Lascaux ou la naissance de l’art, located the birth of humanity in the cave paintings of Lascaux, the first known example of prehistoric cave painting. Discovered in 1940, the cave came to represent, for many intellectuals of the post-war years, the origin of humanity as well as the origin of art. This article problematizes the notion of transgression in its relation to aesthetics and aesthetic creation in Bataille’s writings on Lascaux, exploring his developments on alteration, transfiguration, uselesness and “the inform”. For Bataille, the paintings in the cave became the symbol of the origin of art as the origin of transgression, as well as the idea of the origin as transgression itself. Key words: Georges Bataille, Lascaux, transgression, cave painting, art, alteration.